2020
DOI: 10.1158/1535-7163.mct-20-0385
|View full text |Cite
|
Sign up to set email alerts
|

Emerging CAR-T Cell Therapy for the Treatment of Triple-Negative Breast Cancer

Abstract: Financial support: All authors are paid employees of the Janssen Pharmaceuticals, Johnsons & Johnson Group of companies and receiving salary and other compensation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
73
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(81 citation statements)
references
References 114 publications
(93 reference statements)
1
73
0
2
Order By: Relevance
“…Cell surface antigens, including RTKs (e.g., AXL, EGFR, MET, ROR, etc. ), which are overexpressed in TNBCs, are promising targets for CAR-T cell therapy [ 597 ]. Since in vitro and in vivo studies have demonstrated the efficacy of CAR-T cell therapy against TNBC cells, combination approaches may further expand the therapeutic opportunities in the future.…”
Section: Combination Strategy For Overcoming Egfri Resistance In Tnbcmentioning
confidence: 99%
“…Cell surface antigens, including RTKs (e.g., AXL, EGFR, MET, ROR, etc. ), which are overexpressed in TNBCs, are promising targets for CAR-T cell therapy [ 597 ]. Since in vitro and in vivo studies have demonstrated the efficacy of CAR-T cell therapy against TNBC cells, combination approaches may further expand the therapeutic opportunities in the future.…”
Section: Combination Strategy For Overcoming Egfri Resistance In Tnbcmentioning
confidence: 99%
“…FDA-approved therapies that target the DNA damage repair mechanism of TNBC, such as PARP inhibitors, have shown minimal clinical benefit yet [ 48 , 49 ]. A recent clinical precedent has been established by FDA approval for two TNBC immunotherapies, including an antibody-drug conjugate and an anti-PD-L1 agent [ 50 , 51 ]. The discovery of six molecular subtypes of TNBC, one of which is an immunomodulatory subtype, further accelerated the development of immunotherapeutic strategies for this disease indication [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…The discovery of six molecular subtypes of TNBC, one of which is an immunomodulatory subtype, further accelerated the development of immunotherapeutic strategies for this disease indication [ 52 ]. In addition, chimeric antigen receptor (CAR)-T cell therapy, a type of adoptive cell therapy that combines the antigen specificity of an antibody with the effector function of T cells, has emerged as a promising immunotherapy strategy to improve the survival rate of TNBC patients [ 50 , 53 ]. In our study, in the triple-negative subtype, CD8+ T cells were significantly lower in BCBM than in primary BC.…”
Section: Discussionmentioning
confidence: 99%
“…Despite that, some potential neoantigen targets are being tested in phase II trials. Chimeric CAR-T-cells targeting both antigenic target and other TME cells are also being developed to overcome the immunosuppressive TME [208].…”
Section: Therapies Targeting the Tumor Microenvironmentmentioning
confidence: 99%